Theremin, gestos e intersecções audiovisuais - Baptista, Julia Teles (2023)
This work investigates the potentialities of the musical instrument theremin and of the gesture of playing it in the context of performative arts. Seeking an approach beyond the traditional use of the device (which is mainly used to play melodies), we intend to discuss other possible gestures, considering its specificity of being played "in the air", without the need for physical contact between performer and instrument. Furthermore, we want to propose an expansion of its use to the visual field, with the instrument also acting as a controller for interactive stage lighting in dance performances. Discussing the history of the instrument and of other gestural interfaces built by Liev Theremin in the 1920s, we seek to confront different conceptualizations of the gesture (by authors such as Vilém Flusser, Andre Leroi-Gourhan and others) and comment on the creative process leading to the performance Éter, created by the author of this study in partnership with artist Camila Venturelli. We seek to elucidate some of the following questions: What does the gesture of playing theremin inaugurate in the instrumental tradition? What are the main differences between the gesture of playing a theremin in a melodic, traditional way and other possible gestures? What happens when we play the instrument with our whole body, other body parts, or more than one body? What body-sound-light relationships can be established in relation to the instrument's invisible electric field? How to choreograph gestures based on these relationships?